Challenges and career consequences of internationally educated nurses: Empirical research qualitative - Chiharu Miyata (Wiley, 2023)
Abstract Aim To explore challenges, and career consequences of internationally educated nurses, and considerations of development policy, education, and support for them from the perspective of nursing administrators. Design This study applied a qualitative description design. Methods A semi‐structured interview guideline were used, interviewed eight internationally educated nurses and nine nursing administrators were chosen based on a purposive sampling method. Each interview was recorded and transcribed, after which it was analyzed using the qualitative content analysis method. Results Three categories were extracted as the challenges and career consequences, and the support they expect to organization of internationally educated nurses: "Language barrier," "Transition to recover their confidence and increase motivation," and "Close support from many quarters". Four categories were extracted as key considerations of support to internationally educated nurses that nursing administrators had recognized: "Clarification of career path", "Support for insufficient language skills", "Support for their career reconstruction", "Comprehensive support". This research found that nursing administrators had recognized necessity of adequate work‐related support, it almost met the needs of internationally educated nurses. we need to make a clear policy how to develop internationally educated nurses as valuable human resource based on the evidence of further research relate to support practiced at each facility. Patient or Public Contribution There was no patient and public involvement since I only conducted interview to nurses in this study.